Hearing and vision screening tools for long-term care residents with dementia: protocol for a scoping review - McGilton, Katherine S (BMJ Open, 2016)
INTRODUCTION: Hearing and vision loss among long-term care (LTC) residents with dementia frequently goes unnoticed and untreated. Despite negative consequences for these residents, there is little information available about their sensory abilities and care assessments and practices seldom take these abilities or accessibility needs into account. Without adequate knowledge regarding such sensory loss, it is difficult for LTC staff to determine the level of an individual's residual basic competence for communication and independent functioning. We will conduct a scoping review to identify the screening measures used in research and clinical contexts that test hearing and vision in adults aged over 65 years with dementia, aiming to: (1) provide an overview of hearing and vision screening in older adults with dementia; and (2) evaluate the sensibility of the screening tools. METHODS AND ANALYSIS: This scoping review will be conducted using the framework by Arksey and O'Malley and furthered by methodological enhancements from cited researchers. We will conduct electronic database searches in CENTRAL, CINAHL, EMBASE, MEDLINE and PsycINFO. We will also carry out a ‘grey literature’ search for studies or materials not formally published, both online and through interview discussions with healthcare professionals and research clinicians working in the field. Our aim is to find new and existing hearing and vision screening measures used in research and by clinical professionals of optometry and audiology. Abstracts will be independently reviewed twice for acceptance by a multidisciplinary team of researchers and research clinicians. ETHICS AND DISSEMINATION: This review will inform health professionals working with this growing population. With the review findings, we aim to develop a toolkit and an algorithmic process to select the most appropriate hearing and vision screening assessments for LTC residents with dementia that will facilitate accurate testing and can inform care planning, thereby improving residents’ quality of life.